ANALISIS PENGARUH DUKUNGAN ATASAN, MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KARIR PLATEAU (STUDI PADA KARYAWAN BANK MAYAPADA KANTOR CABANG SEMARANG) - 11.42.02.0058, Daniel Adi Setya Rahardjo (Jurnal Mahasiswa Pasca Sarjana, 2013)
Career plateau is a point in a career that is likely to get very little promotion hierarchy. Someone will have a career plateau due to employee dissatisfaction and low competitiveness of the organization. Career plateau phenomenon in PT. Mayapada Semarang branch contained 20% of employees are not able to increase his career. It is influenced because of the lack of supervisor support and motivation that exist within the PT. Mayapada Bank Branch Semarang. The purpose of research is to analyze the support and motivation to work with the boss mediation job satisfaction on employee career at Bank Mayapada Plateau Branch Semarang. The population inthis study wereemployees ofBankBranchSemarang, without elaborating. Samplingtechniquein this studyisusingpurposivesamplingwith a sample of93people. Analysis tools usedin this studyusing multiple linear regression. The results of this study it can be concluded that support supervisor and work motivation has a positive effect on employee job satisfaction. Supervisor support, work motivation and job satisfaction negatively affect employee career plateau. Job satisfaction does not mediate the influence of supervisor support and motivation to work towards a career plateau Mayapada Bank Branch employees Semarang. Keywords: supervisorsupport, work motivation, job satisfactionandcareerplateau